A preliminary account of Burseraceae in Thailand - Pooma, Rachun (Thai Forest Bulletin (Botany), 2014)
A preliminary account of Thai Burseraceae is presented. Five genera and 20 species are found in the country. Some species which are commonly found near the Thai-Malaysian border, and which may occur in Thailand, are also included in the account. A description of the family is provided together with keys to genera and to species. Synopses of the species is given. Further study is required. especially the examination or more herbarium specimens and extra tield work near theThai-Malaysian border.